Features of geriatric status in elderly patients with osteoarthritis combined with neuropathic pain: data from the Russian epidemiological study EVKALIPT - A. V. Naumov; N. M. Vorobieva; N. O. Khovasova; O. N. Tkacheva; Yu. V. Kotovskaya; E. V. Selezneva; L. H. Ovcharova (Современная ревматология, 2022)
The main symptoms of osteoarthritis (OA) are pain and dysfunction of the joints. Neuropathic pain (NP) occurs in more than half of patients with OA, it is refractory in nature and is the cause for seeking medical advice more frequently, poor quality of life and disability.Objective: to evaluate the frequency of NP and its relationship with geriatric syndromes (GS) in patients with OA aged 65 years and older. Patients and methods. The subanalysis of the study EVKALIPT included 2286 patients with OA and chronic pain syndrome. All patients underwent a comprehensive geriatric assessment (CGA) and diagnostics of NP using the DN4 questionnaire.Results and discussion. The prevalence of NP in patients with OA was 22.7%. Patients with OA and NP more often experienced pain of any localization with a large number of tender points, they had a higher frequency and intensity of pain syndrome, they more often took analgesics and noted limitations in daily life. When conducting a correlation analysis, correlations of medium strength were found between the sum of scores according to DN4 questionnaire and the pain intensity assessment on a numerical rating scale at the time of examination (r=0.26; p<0.001) and in the previous 7 days (r=0.29; p<0.001). CGA data in patients with OA and NP demonstrated worse geriatric status and a higher incidence of GS. The most common GSs were basic (81%) and instrumental (64%) dependence in everyday life, senile asthenia (70%), urinary incontinence (69%), depression (69%) and cognitive impairment (67%). Multivariate analysis showed that, in addition to age, the presence of NP was independently associated with sensory deficits, depression, falls, urinary incontinence, and bedsores (odds ratio 1.77–2.49). Patients with NP were more likely to use mobility aids, absorbent underwear, and orthotics.Conclusion. NP was diagnosed in 22.7% of OA patients aged 65 years and older. Such patients have worse functional status, they are more often diagnosed with a number of GSs.